Les découpages municipaux en Europe : la France est-elle vraiment une exception ? - Jean-Baptiste Grison (EchoGéo)
This paper questions the particularities of French local governance in comparison with other local administrative network in Europe. National data are first considered. The national administrative profiles shows different categories of countries, and some specificities in the French case. Second, a distinctive approach to the smaller municipalities in each country allows a different vision of the divergences. Moreover, a look at some national case studies, sometimes shows important regional variations. Third, all these observations result in a new typology of European local administrative systems. With this typology, the French exception becomes more nuanced, in regards to several other exceptions. France is not the only country to include very small administrative divisions. Furthermore, all local administrative systems have to take the smaller local communities into consideration.